2022
DOI: 10.3390/ijerph19031526
|View full text |Cite
|
Sign up to set email alerts
|

Extended Warranty Strategy and Its Environment Impact of Remanufactured Supply Chain

Abstract: To reduce environmental pollution, the government has issued relevant laws and regulations, and more and more enterprises engage in remanufacturing and recycling used products. Trade old for new and trade old for remanufactured have become marketing means to promote product recycling. The extended warranty service is used to promote the recycling of waste products. To design an optimal extended warranty service strategy and analyze its environment impact in a remanufactured supply chain, game theory is used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 82 publications
(117 reference statements)
0
8
0
1
Order By: Relevance
“…In addition, the researchers believe that there is still considerable room for future research, such as in-depth research on the relationship between online and offline word-of-mouth in social media and its impact on consumers' decision-making process for purchasing or adopting remanufactured products. Furthermore, referring to Zhang et al (2022), trade old for remanufactured has become a marketing tool to promote product recycling. Extended Warranty Services are used to facilitate recycling of end-of-life products.…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
“…In addition, the researchers believe that there is still considerable room for future research, such as in-depth research on the relationship between online and offline word-of-mouth in social media and its impact on consumers' decision-making process for purchasing or adopting remanufactured products. Furthermore, referring to Zhang et al (2022), trade old for remanufactured has become a marketing tool to promote product recycling. Extended Warranty Services are used to facilitate recycling of end-of-life products.…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
“…Liu et al [31] considered an extended producer responsibility and investigated the relationship between fairness concerns and the pricing-based responsibility transmission. Zhang et al [32] investigated whether the E-commerce platform provides extended warranty service and found that the new and remanufactured products with extended warranty service strategy are the best choice. The existing literature on extended warranty service strategies has mostly investigated the impacts of extended warranty services provided by a specific provider on supply-chain decisions.…”
Section: Extended Warranty Service Strategiesmentioning
confidence: 99%
“…Cost structure. The cost of the extended warranty is dependent on the product failure probability and extended warranty coverage [8,32]. The cost of providing extended warranty is a convex function of the extended warranty coverage, and it is formulated as c e = αT 2 [36,37].…”
Section: Problem Description and Model Assumptionsmentioning
confidence: 99%
“…Fan et al (2022) analyzed if and when manufacturers adopt a collect-to-consign strategy and examined optimal trade-in channel options. Zhang et al (2022) used the game theory to study the optimal extended warranty service strategy in the remanufacturing supply chain and analyzed its environmental impact.…”
Section: Literature Review and Contributionmentioning
confidence: 99%